A convenient approach to an advanced intermediate toward the naturally occurring, bioactive 6-substituted 5-hydroxy-4-aryl-1H-quinolin-2-ones - Simonetti, Sebastián Osvaldo (2016)
Fil: Fil: Simonetti, Sebastián Osvaldo. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Química Rosario (IQUIR-CONICET); Argentina.